Cook Islands : Technical Assistance Report-Macroeconomic, Financial, and Structural Policies. (IMF Staff Country Reports; Country Report, 2020)
A mission was requested by the New Zealand authorities to the Cook Islands to focus on policy options for transitioning to high-income status, financial sector stability and regulatory framework, and debt sustainability.1 It evaluated these issues in the context of the medium-term outlook and against the context of a recently developed fiscal framework. The Cook Islands is a self-governing territory in free association with New Zealand, but it is not an IMF member (Box 1).